HIGHLY-PRODUCTIVE ADC WITH COMBINED BALANCING - BAHATSKYI, Valentine; OBERTYUKH, Maxim; ZAKHARCHENKO, Serhii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Today analog-to-digital converters are used in computing and control systems which have greatly expanded in the era of the digital revolution. Increasing the accuracy, speed, energy efficiency, and reliability of analog-to-digital converters is extremely important. One of the most classic types of analog-to-digital converters is the sequential approximation and tracking type ADCs. The conversion time of the tracking type ADC is variable and is determined by the difference between the two readings of the input voltage. Therefore, combining the tracking approach and the method of successive approximation in the case of sharp jumps in the input signal allows you to significantly improve the conversion characteristic. Also the use of redundant counting systems for the weights of the ADC digits has significant advantages, which makes it possible to significantly increase the linearity of the conversion characteristic. The methods of construction of ADCs working on the principle of successive approximation and analog-digital converters whose operation algorithm is tracking are considered. A method of constructing a combined type ADC is proposed, which combines a follow-up conversion algorithm and a sequential approximation algorithm, which allows to improve the characteristics of ADC conversion. The expediency of using a combined type of redundant positional counting systems in ADCs has been proven. The analyzed property of redundant positional counting systems, which is inherent in them when the real weights of the digits deviate from their theoretical values, ensures the absence of "gaps" in the conversion characteristic, as well as the ability to perform the procedure of self-calibration of the weights of the ADC digits, thereby significantly improving the linearity of the conversion characteristic. It is indicated that even with the lengthening of the bit grid for ADCs built on the basis of redundant positional counting systems, their performance does not decrease.
Keywords: combined balancing; weight redundancy; ADC